Dehydration of 1, 5‐Pentanediol over Na‐Doped CeO2 Catalysts. Issue 5 (6th February 2018) - Gnanamani, Muthu Kumaran; Jacobs, Gary; Martinelli, Michela; Shafer, Wilson D.; Hopps, Shelley D.; Thomas, Gerald A.; Davis, Burtron H.
Abstract: The effects of CeO2 doped with Na on the dehydration of 1, 5‐pentanediol were studied by using a fixed‐bed reactor at two different temperatures (350 and 400 °C) and atmospheric pressure. For characterization, BET surface area, hydrogen temperature‐programmed reduction, CO2 temperature‐programmed desorption, and diffuse reflectance infrared Fourier transform spectroscopy techniques were utilized. The conversion of the diol on CeO2 was found to depend on Na loading. The selectivity to the desired product (i.e., unsaturated alcohol) increased and the selectivity to undesired products (i.e., tetrahydropyran, tetrahydropyran‐2‐one, cyclopentanol and cylopentanone) decreased with increasing Na content on CeO2 . The basicity of hydroxyl groups or surface oxygen on CeO2 was altered with the addition of Na, and controlled the dehydration reaction pathway. Abstract : On a sodium basis : Na‐doped ceria converts 1.5‐pentanediol more selectively to unsaturated alcohol than undoped ceria. The basicity of catalysts determines the reaction pathway. Oxygen vacancies on the surface of ceria are the primary adsorption sites for alcohols.